1998
DOI: 10.1007/s002849900354
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of galE Gene Inactivation on Lipopolysaccharide Profile of Helicobacter pylori

Abstract: The galE gene product, UDP-galactose 4-epimerase, mediates the incorporation of galactose in extracellular polysaccharide materials such as the O-side chain of lipopolysaccharide (LPS). The O-side chain in H. pylori LPS has been shown to cross-react with Lewis x and/or y blood group antigens, suggesting its potential involvement in H. pylori-linked autoimmune disease. To study its role in H. pylori LPS biosynthesis, the galE gene was cloned, sequenced, and a galE-knockout H. pylori strain was constructed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…LPS structure (4,5,46) and biochemical data (15,30,36,44) indicated that FlaA1 and WbpB were not LPS biosynthetic enzymes per se in H. pylori. Disruption of their genes nevertheless significantly reduced O-antigen production and resulted in the formation of altered core LPS (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS structure (4,5,46) and biochemical data (15,30,36,44) indicated that FlaA1 and WbpB were not LPS biosynthetic enzymes per se in H. pylori. Disruption of their genes nevertheless significantly reduced O-antigen production and resulted in the formation of altered core LPS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, neither the 4-keto intermediate nor its reduced derivative are present in the LPS of H. pylori (4,5,46). In addition, all genes involved in the biosynthesis of the precursors necessary for LPS assembly have been identified (30,36,44) and are distinct from flaA1 and wbpB. Consequently, although it is expected that flaA1 and wbpB might affect LPS synthesis based on sequence homologies, such an effect is not anticipated to occur directly via production of LPS sugar precursors.…”
mentioning
confidence: 99%
“…In previous studies, the galE mutant of Vibrio cholerae, whose O antigen does not include galactose, did not have an altered LPS profile (26), while galE mutants of other bacteria, such as Neisseria meningitidis and Helicobacter pylori, were found to produce truncated LPS molecules that lacked galactose (16,19). Bramanti et al reported that galactose accounted for 25.3% of the total monosaccharides of LPS in P. gingivalis strain 33277 (4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we constructed isogenic H. pylori P1 mutants defective in the galE gene (hp360) encoding a UDP-glucose-4-epimerase, or the pmi gene (also called rfbM or hp43) encoding a bifunctional mannose-6-phosphate isomerase/GDPmannose pyrophosphorylase, both of which are involved in LPS biosynthesis (8). The galE gene of strain P1 was disrupted with plasmid pGH26 (24), and the pmi gene was disrupted with plasmid pDHO25::TnMax5-3 (18). Both mutations resulted in the production of a RecA protein without an apparent modification (Fig.…”
Section: Size Variation Of Thementioning
confidence: 99%